Losev’s Eidetic Dialectic: The Structuring of Being and Anagogical Cognition - Kosykhin, Vitaly (Stasis, 2013)
Alexei Losev dared to make the radical gesture of integrating Platonist hermeneutics into modern thinking by turning to the genuine tradition of ancient Platonism, especially to the works of Iamblichus and Proclus. The article compares the dialectical approaches of Hegel and Losev, and analyzes the problem of negativity in dialectical discourse. The eidetic dialectic of part and whole, based on the contemplative and anagogical mode of cognition, is considered as a real alternative to negative reductionism and nihilism in contemporary philosophy.